1958
DOI: 10.1002/jsfa.2740090505
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur in soils. III.—A study of the readily soluble sulphate content and of the total sulphur content of soil

Abstract: Results are given of a survey of the readily soluble sulphate content and of the total sulphur content of soils of various categories. These results have been correlated with the results of ‘routine’ analytical determinations. The close relationship found to exist between pC and readily soluble sulphate stresses the importance of the sulphate ion in the physico‐chemical equilibrium of soil. Published results of other workers are reviewed, and comparisons drawn with the results obtained in the present survey. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1960
1960
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Sulphur removed in the crops was therefore assumed equal to additions from the atmosphere. Little (1958) showed that there has been no accumulation of sulphur in the soil from plots given sulphate fertilizers.…”
Section: A Model To Explain Lime Losses From Broadbalk Plotsmentioning
confidence: 97%
“…Sulphur removed in the crops was therefore assumed equal to additions from the atmosphere. Little (1958) showed that there has been no accumulation of sulphur in the soil from plots given sulphate fertilizers.…”
Section: A Model To Explain Lime Losses From Broadbalk Plotsmentioning
confidence: 97%
“…In 1945 Evans and Rost (4) pointed out that sulPhul was an element unjustifiably neglected by soit workers. The situation has changed little irtiS ye"rsl Tfiis neglecl may be attributed in part to-the fact.that studics undertaken in the ""t'ii.t pari of the century indicated that soil and atmospheric soutces were in *dr, .rr., able to supply croP needs for this element, ,l.ra n part to the lack of convenient methbis for determining the element (10,19).…”
Section: Introductionmentioning
confidence: 99%
“…In Poland Boratynski & Zietecka (1974) found that retention of sulphate added in superphosphate was strongly dependent on the clay content of the soil. Jensen (1963) showed that it was impossible to build up reserves of S in the non-retentive sandy soils of Denmark through the use of superphosphate, and concluded that S must be applied regularly in the same manner as N. Little (1958) also observed no build-up of soluble S from fertiliser applications on English soils.…”
Section: Downloaded By [University Of Toronto Libraries] At 13:01 22 mentioning
confidence: 92%